7 Habits for Effective Human Development - Thangthongmadan, Sathien (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
The objectives of the study Article 7 Habits for Effective Human Development are as follows: 1) to study concepts about humans and adaptation, 2) to study the details of 7 habits, and 3) to analyze 7 habits for human development to be effective. The study is found that man is a social animal, because human beings live together as a group, a society, the coexistence of human beings in society. Human beings have to adapt to survive in society. Adjustment must start from the human adaptation first. Then there is interaction with others. The 7 Habits to develop human beings to be productive s follow 1) You have to start first, 2) start with a clear goal, 3) do the main thing first, 4) win-win thinking, 5) trying to understand others first, 6) coordinating power and 7) practice always ready yourself. Using 7 habits to develop human beings to be effective can be done in 3 levels: 1) self-development level. It can be done by starting first have a clear goal and do the important thing first. 2) The level of creativity with others. It can be done by think win-win, always understand others first. and coordinate to increase power 3) level of review Self improvement It can be done by training yourself to be always ready. If you can do all these 7 steps, it will be a highly productive human being in society.